Spook country [compact disc, unabridged] - Gibson, William, 1948- (Penguin Audio, 2007)
A multilingual man engages in sensitive information transfers from his single-room apartment, while a journalist frets over her start-up magazine's censure of its own promotions, and a prescription drug addict wonders about the military connections of an enigmatic benefactor.